2012
DOI: 10.1021/nn2050032
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Photothermal Effects in Plasmonic Nanostructures

Abstract: Photothermal effects in plasmonic nanostructures have great potentials in applications for photothermal cancer therapy, optical storage, thermo-photovoltaics, etc. However, the transient temperature behavior of a nanoscale material system during an ultrafast photothermal process has rarely been accurately investigated. Here a heat transfer model is constructed to investigate the temporal and spatial variation of temperature in plasmonic gold nanostructures. First, as a benchmark scenario, we study the light-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
326
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(333 citation statements)
references
References 30 publications
7
326
0
Order By: Relevance
“…However, in our case, the NaYF 4 NPs are directly in contact with the plasmonic W 18 O 49 NWs and the nonradiative energy transfer to W 18 O 49 NWs provides an efficient decay channel to quench the upconversion luminescence 31, 32, 33, 34. The time‐resolved luminescence spectroscopy indicated that the lifetimes of 2 I 11/2 → 4 I 15/2 (521 nm), 4 S 3/2 → 4 I 15/2 (545 nm), and 4 F 9/2 – 4 I 15/2 (660 nm) decays for the NaYF 4 :Yb‐Er/W 18 O 49 film were shorter than the corresponding lifetimes obtained from the individual NaYF 4 :Yb‐Er film (Figure S7, Supporting Information).…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…However, in our case, the NaYF 4 NPs are directly in contact with the plasmonic W 18 O 49 NWs and the nonradiative energy transfer to W 18 O 49 NWs provides an efficient decay channel to quench the upconversion luminescence 31, 32, 33, 34. The time‐resolved luminescence spectroscopy indicated that the lifetimes of 2 I 11/2 → 4 I 15/2 (521 nm), 4 S 3/2 → 4 I 15/2 (545 nm), and 4 F 9/2 – 4 I 15/2 (660 nm) decays for the NaYF 4 :Yb‐Er/W 18 O 49 film were shorter than the corresponding lifetimes obtained from the individual NaYF 4 :Yb‐Er film (Figure S7, Supporting Information).…”
mentioning
confidence: 86%
“…Meanwhile, the LSPR‐enhanced localized electric field can interact with the emission electric field of NaYF 4 :Yb‐Er NPs to boost the radiative decay rate of upconversion process 4, 7. However, the direct contact of W 18 O 49 NWs and NaYF 4 :Yb‐Er NPs quenches the upconversion emission to a certain degree due to the nonradiative energy transfer from the NaYF 4 :Yb‐Er NPs (donor) and the adherent W 18 O 49 NWs (acceptor) 31, 32, 33, 34. Moreover, the upconversion luminescence of NaYF 4 :Yb‐Er NPs can also be absorbed by the adjacent W 18 O 49 NWs, which selectively weakens the luminescence intensity depending on the absorption band of W 18 O 49 NWs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 The LSPR traits are strong light absorption, scattering and light field focusing on the NP surface, and are the keystone of the emerging field of plasmonics [2][3][4][5][6][7][8][9][10][11][12] which promises radical breakthroughs in optical storage and transport of information. Strong intensity laser light, on the other hand, interacts with the metal NPs in many more complex ways, which include the self assembly of particles from individual metal atoms, 13 particle reshaping, [14][15][16][17][18][19][20] melting and recrystallization, 21-25 metal growth, 26 and even structural alteration of the dielectric matrix. 27 This photosensitivity is a property of the composite metallodielectric system and depends on the fine details of both the initial NP/host structure and the laser source.…”
Section: Introductionmentioning
confidence: 99%